Epidemiology and costs of severe acute respiratory infection and influenza hospitalizations in adults with diabetes in India - Koul, Parvaiz A; Bhavsar, Amit; Mir, Hyder; Simmerman, Mark; Khanna, Hemant (The Journal of Infection in Developing Countries, 2019)
Introduction: The incidence of diabetes mellitus is increasing rapidly in India. In addition to well-known complications, diabetes increases the risk for hospitalization and death from severe acute respiratory infection (SARI) and influenza. Here we examined the impact of SARI and influenza in Indian adults with diabetes. Methodology: This was a single-center, active surveillance study conducted in Jammu and Kashmir State, India, during the 2015–2016 and 2016–2017 influenza seasons. Adults hospitalized for SARI and receiving at least one diabetes medication were included. Demographics, health care use, and direct costs were collected from medical records and interviews of patients or caregivers. Indirect costs were estimated based on lost earnings and WHO-CHOICE estimates for hospital costs. Results: The study included 192 patients with type 2 diabetes. Median age was 66 years, median body mass index was 26.6 kg/m2, and most patients had comorbidities, especially hypertension and cardiovascular disease (83.9%). Only 32.2% regularly monitored blood glucose or hemoglobin A1C, and median values at admission indicated poor glycemic control for most. Influenza was detected in 8.9% of cases. The median hospital stay for SARI was 8 days, and 22 patients (11.4%) died. Median total costs associated with hospitalization were US$710 (interquartile range, $539–$1067) for SARI patients and US$716 ($556–$1078) for influenza patients, mostly (~75%) from indirect costs. Conclusions: Adults with diabetes in India hospitalized with SARI or influenza are generally older, in poor health, and suffer from poor glycemic control. The costs for their hospitalization and care are substantial.